2018
DOI: 10.1371/journal.pone.0194052
|View full text |Cite
|
Sign up to set email alerts
|

Structure—Function relationships of equine menisci

Abstract: Meniscal pathologies are among the most common injuries of the femorotibial joint in both human and equine patients. Pathological forces and ensuing injuries of the cranial horn of the equine medial meniscus are considered analogous to those observed in the human posterior medial horn. Biomechanical properties of human menisci are site- and depth- specific. However, the influence of equine meniscus topography and composition on its biomechanical properties is yet unknown. A better understanding of equine menis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Neomenisci resembled native meniscus fibrocartilage [44 , 45] in terms of gross appearance ( Fig. 1 ) [45][46][47] . The characteristic wedge-shaped profile was maintained after 5 weeks of culture (Supplementary Fig.…”
Section: Gross Morphology Histology and Immunohistochemistrymentioning
confidence: 99%
“…Neomenisci resembled native meniscus fibrocartilage [44 , 45] in terms of gross appearance ( Fig. 1 ) [45][46][47] . The characteristic wedge-shaped profile was maintained after 5 weeks of culture (Supplementary Fig.…”
Section: Gross Morphology Histology and Immunohistochemistrymentioning
confidence: 99%
“…Furthermore, depth dependent fibril strains are considered to exhibit a fundamental role on tissue stresses [45]. Some human computational meniscus models have already incorporated collagen fibrils and anisotropic material properties to simulate the meniscus’ dynamic behavior [43,52,53,54] Hence, depth- and location specific histologic and mechanical properties will be adopted into the next generation of the FEA model based on data from our previous work [13,55]. Also the currently omitted stabilizing effect of ligaments and adjacent muscles should be included in future approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, collagen fibers in an equine knee meniscus model were shown to be randomly organized in the distal and proximal surface layers [60,61] (Fig. 5(b)), while the innermost layer exhibited circumferentially aligned collagen fibers with parallel alignment in the redred region [60]. Polarized light microscopy [62] and scanning electron microscopy [56] showed that collagen aligned primarily circumferentially of the human and porcine TMJ discs, with the intermediate zone showing alignment anteroposteriorly (Fig.…”
Section: Characterization Studies Of Fibrocartilagesmentioning
confidence: 95%
“…5(c)). GAGs were evenly distributed throughout young equine menisci, whereas samples from older horses showed distinct positive and negative staining locations [60]. IHC determined the presence of hyaluronic acid backbone, keratan sulfate, and chondroitin sulfate in the primate TMJ disc [57].…”
Section: Characterization Studies Of Fibrocartilagesmentioning
confidence: 99%
See 1 more Smart Citation